Determinants of Board and Audit Committee Meeting Frequency: Evidence from Sri Lanka - Pratheepkanth, P. (University of Jaffna Sri Lanka, 2021)
This study aims to look at the factors that influence the frequency of board and audit committee meetings in Sri Lankan listed firms. The factors investigated are connected to the board attributes and ownership structure. Using a sample of 100 Sri Lankan listed firms from 2016 to 2020, this study uses a multiple linear regression model. The frequency of board and audit committee meetings is unrelated to ownership concentration. Both the frequency of board meetings and the frequency of audit committee meetings are negatively correlated with insider ownership. The board and the audit committee activity are positively associated with the proportion of independent directors on the board. The size of the board, as well as the audit committee, is not a significant factor of meeting frequency. There is no significant link between CEO duality and the dependent variables. The size of the audit committee has a positive relationship with the frequency of board or audit committee meetings. This study addresses a gap in the literature by providing a study on the determinants of board and audit committee meeting frequency. It also warns regulators, and practitioners in the emerging countries to pay more attention to CG reforms and enforcement.
Keywords: Board meetings; Audit committee meetings; Corporate governance; Sri Lanka